Miocene slip history of the Eagle Eye detachment fault, Harquahala Mountains metamorphic core complex, west‐central Arizona. Issue 8 (22nd August 2016) - Prior, Michael G.; Stockli, Daniel F.; Singleton, John S.
Abstract: The structural and thermal evolution of major low‐angle normal faults in the Colorado River extensional corridor has been a controversial topic since the pioneering studies of metamorphic core complexes in the early 1980s. We present new geo‐thermochronometry data from the Harquahala Mountains in west‐central Arizona to determine the timing of extension, displacement magnitude, and slip rates along the Eagle Eye detachment fault (EED) during large‐magnitude Miocene extension. Zircon and apatite (U‐Th)/He data (ZHe and AHe, respectively) from 31 samples along a ~55 km extension‐parallel transect indicate active slip along the EED occurred between ~21 ± 1 Ma and ~14 Ma. The spatial extent of ZHe ages and exhumation of the zircon partial retention zone indicated ~44 ± 2 km of total displacement, whereas lithologic similarity and identical U‐Pb ages between correlated footwall rocks in the Little Harquahala Mountains and breccia clasts at Bullard Peak in the NE Harcuvar Mountains indicated ~43–45 km of displacement across the EED. AHe and ZHe data indicated slip rates of ~6.7 + 7.8/−2.3 km/Myr, and ~6.6 + 7.1/−2.0 km/Myr, respectively, both consistent with the duration and displacement estimates. The EED initiated as a listric fault with an ~34 ± 9° dip that decreased to ~13 ± 5° below ~7 km depth. Secondary breakaway development and footwall exposure occurred by ~17 Ma, during active EED slip. Lithologic and geo‐thermochronometric offset constraints show excellent agreement and provided a rare opportunity to fully resolve the timing, rates, and total displacement magnitudes along a major continental detachment fault. Key Points: Total displacement on the Eagle Eye detachment fault is ~44 ± 2 km Apatite and zircon (U‐Th)/He slip rates along the Eagle Eye detachment are ~6.6 + 7.8/−2.3 km/Myr and ~6.6 + 7.1/−2.0 km/Myr, respectively Active extension along the Eagle Eye detachment fault from ~21 ± 1 Ma to ~14 Ma